Radiation exposure and fluoroscopy time in mechanical thrombectomy of anterior circulation ischemic stroke depending on the interventionalist’s experience: a retrospective single center experience - Weyland, Charlotte S.; Hemmerich, Felix; Möhlenbruch, Markus Alfred; Bendszus, Martin; Pfaff, Johannes (European radiology, 2020)
To quantify the influence of interventionalist’s experience on procedure time, radiation exposure, and fluoroscopy time during mechanical thrombectomy (MT) in the anterior circulation.
Gesehen am 28.10.2020
Published online: 11 November 2019